A unified fatigue life calculation based on intrinsic thermal dissipation and microplasticity evolution. (February 2020) - Teng, Zhenjie; Wu, Haoran; Boller, Christian; Starke, Peter
Highlights: High-cycle fatigue strength can be evaluated by one load increase test. Intrinsic dissipation and microplasticity evolution were evaluated. Short term evaluation procedures for the fatigue life of SAE 1045 were calculated. The approach was verified by the experimental results. Abstract: This paper advances a unified approach by evaluating the evolution of the intrinsic thermal dissipation and the microplasticity strain amplitude of SAE1045 steel. The intrinsic dissipation is utilized to understand the fatigue behavior and to link the materials' microstructure evolution directly. The microplasticity strain amplitude is related to a fatigue process and correlated to fatigue life that can be deducted from the change in temperature. With only one load increase test and one constant amplitude test in the present case, an S-N curve can be evaluated being in very good agreement with experimentally determined data obtained the traditional way.